Assembly and comparison of two closely related Brassica napus genomes. Issue 12 (14th June 2017) - Bayer, Philipp E.; Hurgobin, Bhavna; Golicz, Agnieszka A.; Chan, Chon‐Kit Kenneth; Yuan, Yuxuan; Lee, HueyTyng; Renton, Michael; Meng, Jinling; Li, Ruiyuan; Long, Yan; Zou, Jun; Bancroft, Ian; et al.
Summary: As an increasing number of plant genome sequences become available, it is clear that gene content varies between individuals, and the challenge arises to predict the gene content of a species. However, genome comparison is often confounded by variation in assembly and annotation. Differentiating between true gene absence and variation in assembly or annotation is essential for the accurate identification of conserved and variable genes in a species. Here, we present the de novo assembly of the B. napus cultivar Tapidor and comparison with an improved assembly of the Brassica napus cultivar Darmor ‐bzh . Both cultivars were annotated using the same method to allow comparison of gene content. We identified genes unique to each cultivar and differentiate these from artefacts due to variation in the assembly and annotation. We demonstrate that using a common annotation pipeline can result in different gene predictions, even for closely related cultivars, and repeat regions which collapse during assembly impact whole genome comparison. After accounting for differences in assembly and annotation, we demonstrate that the genome of Darmor ‐bzh contains a greater number of genes than the genome of Tapidor. Our results are the first step towards comparison of the true differences between B. napus genomes and highlight the potential sources of error in future production of a B. napus pangenome.